Penerapan Jaringan Serat Optik untuk Pemasaran Digital Usaha Single Parent dengan Memanfaatkan Artificial Intelligence - Yus Natali; Akhmad Hambali; Putri Pramudita Dzikra Afifa Saputra; Andika Maulana Putra; Eka Tiara Rosalya; Muhamad Arjuna Herdiawan; Liestyowati Liestyowati (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Limited digital infrastructure and low financial management capacity hinder the development of home-based businesses operated by members of the Independent Single Parent Community (KSPM) in Belendung Village, Tangerang City. Most members did not maintain structured financial records and relied solely on WhatsApp for marketing due to unstable internet access. This community service program aimed to enhance business capacity through the provision of a Gigabit Passive Optical Network (GPON)-based fiber-optic internet connection, digital bookkeeping training, and mentoring in Artificial Intelligence (AI)-assisted marketing. The program was implemented using a participatory empowerment approach, including infrastructure deployment, six training sessions, and post-training mentoring. Evaluation was conducted through questionnaires, observation, and turnover monitoring. The results show that 70% of participants adopted digital bookkeeping practices after the intervention, and the majority demonstrated improved skills in utilizing AI applications to produce more attractive product photos and promotional materials. Economically, 80% of participants reported an average turnover increase of approximately 5%, while 20% experienced an increase of 10% or more. These findings indicate that integrating digital infrastructure support with technology-based capacity building contributes positively to business management and marketing performance among single-parent entrepreneurs.